2015
DOI: 10.1016/j.apnr.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

To adjust and endure: a qualitative study of symptom burden in older people with multimorbidity

Abstract: Context. Older people with multimorbidity are vulnerable and often suffer from conditions that produce a multiplicity of symptoms and a reduced health-related quality of life.Objectives. The aim of this study is to explore the experience of living with a high symptom burden from the perspective of older community-dwelling people with multi-morbidity.Method. A qualitative descriptive design with semi-structured interviews, including 20 community-dwelling older people with multi-morbidity and a high symptom burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 38 publications
4
38
1
1
Order By: Relevance
“…Participants in our focus group were not able to assign a weight to the different categories because they would like to see their life as a complete picture. These findings are consistent with another study in which patients with multimorbidity preferred a holistic approach to their treatment (Eckerblad, Theander, Ekdahl, Jaarsma, & Hellstrom, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Participants in our focus group were not able to assign a weight to the different categories because they would like to see their life as a complete picture. These findings are consistent with another study in which patients with multimorbidity preferred a holistic approach to their treatment (Eckerblad, Theander, Ekdahl, Jaarsma, & Hellstrom, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Second, the lack of effect of the intervention on symptom burden might be related to underreporting of symptoms by older people. Some symptoms assessed by the MSAS might not have been brought up in discussion by older people themselves since they often assume that old age and symptoms are supposed to go hand in hand (Eckerblad et al 2015a). It has been suggested that old age might cause an age-related response shift in symptoms that cause older people to respond and report symptoms differently than younger people (Riegel et al 2010, Ritchie et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…For the individual, a high symptom burden can lead to a feeling of being dependent, dejected, inadequate and limited (Eckerblad et al . ) and it often results in a high caregiver burden (Kuzuya et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En cuanto a la carga de síntomas, son comunes las manifestaciones de dolor, fatiga [13], cansancio [14], disnea, náusea, vómito, estreñimiento [15], deshidratación, diarrea, limitación física, falta de energía [16], trastornos del sueño [17], trastornos de la alimentación [18,19] y sufrimiento corporal [20].…”
Section: Carga Como Esfuerzo Físico Adicionalunclassified